2011
DOI: 10.1007/s10546-010-9572-2
|View full text |Cite
|
Sign up to set email alerts
|

Stability Dependence of Canopy Flows over a Flat Larch Forest

Abstract: The dependence on atmospheric stability of flow characteristics adjacent to a very rough surface was investigated in a larch forest in Japan. Micrometeorological measurements of three-dimensional wind velocity and air temperature were taken at two heights above the forest, namely 1.7 and 1.2 times the mean canopy height h. Under near-neutral and stable conditions, the observed turbulence statistics suggest that the flow was likely to be that of the atmospheric surface layer (ASL) at 1.7h, and of the roughness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Although, the mixing-layer structures dominating exchange during the foliated period transport these quantities more efficiently. This superposition of turbulent structures within canopy was suggested by Poggi et al (2004) and Kobayashi and Hiyama (2011), and deduced in the orchard canopy from the spectral analysis of the wind velocity components (Dupont and Patton, 2012) .…”
Section: Free Convection Regimementioning
confidence: 75%
See 1 more Smart Citation
“…Although, the mixing-layer structures dominating exchange during the foliated period transport these quantities more efficiently. This superposition of turbulent structures within canopy was suggested by Poggi et al (2004) and Kobayashi and Hiyama (2011), and deduced in the orchard canopy from the spectral analysis of the wind velocity components (Dupont and Patton, 2012) .…”
Section: Free Convection Regimementioning
confidence: 75%
“…This speculation is consistent with Li and Bou-Zeid's (2011) recent study over natural surfaces (a lake and a vineyard), who also suggested that with increasing instability the transport dissimilarity between momentum and scalars could be explained through modification of the near-neutral surface atmospheric boundary layer's hairpin vortices and hairpin packets and their evolution into upward-and downward-moving thermal plumes. In sparse canopies, Poggi et al (2004) and Kobayashi and Hiyama (2011) suggested that mixing-layer type structures might also coexist with traditional atmospheric surface layer (ASL) turbulence. Forest heterogeneities at scales similar to canopyheight may further modify the efficiency of those turbulent structures at exchanging momentum (Bohrer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%